Application of controlled fermented amaranth supplemented with purslane (Portulaca oleracea) powder to improve technological functionalities of wheat bread - Parvin Shayesteh Kia; Alireza Sadeghi; Mahdi Kashaninejad; Maryam Zarali; Morteza Khomeiri (Applied Food Research, 2024)
Application of controlled sourdough (SD) containing protective starter cultures in combination with vegetable powders is an emerging approach to improve wheat bread quality and shelf-life. In the present study, predominant lactic acid bacteria (LAB) isolated from fermented amaranth were screened based on their antifungal activity against Aspergillus niger. Then, the selected LAB isolate (Levilactobacillus brevis) was used as starter culture in controlled fermented amaranth (CFA) containing purslane powder (PP) to produce enriched wheat bread. Supplemented wheat bread with CFA showed the lowest crumb hardness compared to the other enriched samples. Furthermore, combined application of CFA and PP improved textural features rather than the PP alone. The lowest amount of surface moldiness (35.00 %) was also belonged to the sample containing CFA, which was significantly (P < 0.05) lower than those of the other samples. Meanwhile, PP added breads received higher overall acceptability compared to those of the other produced samples. Accordingly, combined application of CFA and PP can be used as a simple and efficient approach to improve the quality characteristics of wheat bread.